Supporting physical training in healthy older adults through biocybernetic adaptation and exergaming - Muñoz Cardona, John Edison (2018)
Physical inactivity in older adults is commonly associated with the development of chronic diseases, poor maintenance of functional status, possible cognitive declines and the loss of physical independence. With the aim of reducing the social and economic burdens generated by the high percentages of older adults in the population, active aging programs have been intensively promoted. These programs, however, suffer from low rates of adherence and a lack of exercise’s personalization that end up in demotivated older adults. Exercise videogames (Exergames) have been established as a fun and enjoyable method to promote physical activity, by using competition, timely feedback, and fun, they counteract the monotony of exercise routines. Although frequently attractive, the use of Exergames for exercise promotion in older adults still faces challenges in demonstrating effectiveness regarding functional fitness, cognitive functions, and game user experience. Moreover, the long-term effects of using Exergames as a structured exercise program in the older population have been rarely investigated. To tackle these limitations in Exergaming research, this thesis uses two different Human-Computer Interaction (HCI) techniques: humancentered design and physiological computing. The main objective is to maximize Exergaming effectiveness via: i) providing a more personalized, diversified and enjoyable game experience through custom-made Exergames and ii) optimizing the body responses while exercising with a physiologically intelligent software layer. First, a set of four Exergames that covers aerobic endurance, muscular strength and motor ability fitness domains were carefully designed via contextual design. Secondly, the biocybernetic loop construct from physiological computing is used to improve the cardiovascular performance of older adults through an Exergame that adapts its difficulty based on game performance and exertion levels, thus persuading players to exert in the desired and recommended levels. Two cross-sectional and two longitudinal controlled studies were completed in local senior gymnasiums with active older adults addressing multiple research questions to unveil the role of customized and adaptive Exergames in promoting physical activity. We demonstrated how attractiveness and effectiveness can be successfully combined in Exergaming design to deliver encouraging and motivating exercises that are equivalent (or sometimes better) to conventional training methods. Moreover, we illustrated the design of a set of physiological computing software tools that can be extensively used for biocybernetic adaptation in videogames, and physiological signal post-processing and interpretation.